The beginnings of the Teutonic state in the light of the latest studies - Wiewióra, Marcin (Archaeologia Historica Polona, 2020)
In 2016–2018, non-invasive and archaeological research was carried out in historical Chełmno Land in north-central Poland as part of the ‘Castra Terrae Culmensis, at the edges of the Christian world’ (project ‘Castra Terrae Culmensis – na rubieży chrześcijańskiego świata’), whose main aim was to clarify key questions regarding the beginnings of the State of the Teutonic Order in Prussia. Discoveries included the remains of a previously unrecognised stronghold founded in the 1230s and a castle in Unisław that was the residence of the Teutonic commandry beginning in the 1280s. After a search of lasting more than 100 years, the relics of Chełmno, the oldest Teutonic city after Toruń, were also discovered. The article presents the results of geophysical, archaeological and geomatic analyses that confirm historical records in the 14th-century Teutonic Chronicle and helped to reconstruct the history of the oldest Teutonic earth-and-timber strongholds and cities chartered under Chełmno law stood.